Superiority of local antimoniate over systemic liposomal amphotericin B therapy in a Leishmania infantum cutaneous leishmaniasis. Issue 4 (August 2015) - Murat, Jean-Benjamin; Maubon, Danièle; Ravel, Christophe; Templier, Isabelle; Epaulard, Olivier
Abstract : Introduction: The therapeutic choice for treating cutaneous leishmaniasis (CL) can be difficult, notably in countries where autochthonous cases are rare. In France, CL is mostly due to imported cases. Leishmania infantum, which is the endemic species in the French south-eastern region, is usually responsible for visceral leishmaniasis but rarely causes the autochthonous cutaneous form of the disease. Intralesional injection of antimonials seems to be the most recommended therapy in the latter case, but particular situations can justify the use of systemic amphotericin B (AmB). Case presentation: We report and illustrate a French case of locally acquired CL due to L. infantum that was surprisingly unresponsive to systemic AmB, with clinical worsening and parasitic invasion of the lesion. Thereafter, the patient was successfully treated by intralesional pentavalent antimonial. Conclusion: This case supports the choice of intralesional therapy as the first therapeutic option in L. infantum CL, an infrequent situation in France.